Management of adrenocortical carcinoma in Western Australia: a perspective over 14 years. Issue 1 (5th July 2020) - Leong, David; Nyantoro, Munyaradzi; Shedzad, Hira; Robins, Peter; Henley, David; Ryan, Simon; Nguyen, Hieu; Lisewski, Dean
Abstract: Background: Adrenocortical carcinoma is a rare but aggressive form of endocrine neoplasm that confers a poor prognosis. To date, the only Australian data published is from New South Wales. This paper describes our experience in Western Australia with a focus on surgical approach and outcomes. Methods: A retrospective study of patients treated for adrenocortical carcinoma in Western Australia over 14 years was performed. Results: Over the 14‐year period, a total of 33 patients underwent surgery for adrenocortical carcinoma. Resection outcomes were superior in an open en bloc approach with an 85% R0 margin ( P  = 0.007). Local recurrence rates were lowest in an open en bloc approach (11%) compared to laparoscopic (75%). Multivariate analysis showed that an en bloc resection is highly correlated with an R0 resection ( P  < 0.05) and significantly associated with lower (odds ratio = 0.06) local recurrence ( P = 0.009). Higher volume surgeons (>5 cases) had lower operative times and blood loss. Compliance with mitotane was significantly improved with close monitoring of levels. The European Network for the Study of Adrenal Tumours (ENSAT) stage at presentation was most predictive of long‐term survival with 100% of stage I patients alive compared to 53% of stage II, 25% of stage III and 17% of stage IV patients at the end of the follow‐up period. Conclusion: An open en bloc approach with a low threshold for multi‐visceral resection performed by high volume surgeons have improved outcomes in local recurrence, operative times and blood loss. Abstract : Adrenocortical carcinoma is a rare but aggressive neoplasm that confers a poor prognosis. This article describes the management of adrenocortical carcinoma in Western Australia over the last 14 years and a review of the literature. Achieving an R0 resection is the key in reducing local recurrence which is best performed by high‐volume centres. The ENSAT stage is most predictive of overall survival